Effect of protein source and level of urea supplementation on performance and rumen fermentation dynamics in feedlot lambs - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2021)
Dissertation (MSc Agric (Animal Science: Animal Nutrition))--University of Pretoria, 2021.